Mapping the Socioeconomic Resilience of Vulnerable Groups in Makassar City - Henni Zainal; Fitriana Fitriana (Public Resource Innovation Management and Excellence, 2025)
The economic crisis is a complex phenomenon that has the potential to shake the social and economic stability of society, especially vulnerable groups. This study aims to analyze the level of socioeconomic resilience of vulnerable communities in Makassar City in facing the impact of the economic crisis. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The data analysis technique used is the theory of Miles and Huberman. The results show that the level of socioeconomic resilience of vulnerable communities in Makassar City varies, influenced by factors such as income level, education, access to public services, and the strength of social networks. The economic crisis tends to worsen the socioeconomic conditions of vulnerable groups. However, several adaptation strategies such as livelihood diversification through strengthening the MSME sector, improving the quality of education and health, saving expenses, and social support have been proven to help increase their resilience. These findings provide important implications for the government in formulating more responsive and sustainable public policies to strengthen the socioeconomic resilience of vulnerable communities in facing future economic crises.